Can AI Predict Cancer Recurrence from Molecular Data? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The prediction of cancer recurrence is a critical aspect of oncology, influencing treatment decisions and patient outcomes. Traditionally, clinicians have re...
Keywords: Precision Medicine and Genomics; Predict; Cancer; Recurrence; Artificial Intelligence; Machine Learning; Deep Learning